Conceitos Modernos Sobre Obesidade - Rozenberg, Samuel (2023)
A review was made of the metabolism stressing the study of lipogenesis and lipolysis as wall as the interrelation of fatty acids with glucose in the metabolism energy homeostasis in the light of recently acquired knowledge. The causes of obesity were analysed stressing the genetic predisposition in the biochemical anomalies of the fatty acids and carbohydrates. It was emphasized that the really efficacious treatment must be preventive, taking into account not only the genetic, but the emotional and social factors as well. A scheme was presented for the treatment of severe obesity by intermittent fast.